Development of a risk classification system combining TN-categories and circulating EBV DNA for non-metastatic NPC in 10, 149 endemic cases. (October 2021) - Chen, Fo-Ping; Lin, Li; Liang, Jin-Hui; Tan, Sze Huey; Ong, Enya H.W.; Luo, Ying-Shan; Huang, Luo; Sim, Adelene Y.L.; Wang, Hai-Tao; Gao, Tian-Sheng; Deng, Bin; Zhou, Guan-Qun; et al.
Background: The objective of this study was to construct a risk classification system integrating cell-free Epstein-Barr virus (cfEBV) DNA with T- and N- categories for better prognostication in nasopharyngeal carcinoma (NPC). Methods: Clinical records of 10, 149 biopsy-proven, non-metastatic NPC were identified from two cancer centers; this comprised a training ( N  = 9, 259) and two validation cohorts ( N  = 890; including one randomized controlled phase 3 trial cohort). Adjusted hazard ratio (AHR) method using a two-tiered stratification by cfEBV DNA and TN-categories was applied to generate the risk model. Primary clinical endpoint was overall survival (OS). Performances of the models were compared against American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) 8th edition TNM-stage classification and two published recursive partitioning analysis (RPA) models, and were validated in the validation cohorts. Results: We chose a cfEBV DNA cutoff of ⩾2, 000 copies for optimal risk discretization of OS, disease-free survival (DFS) and distant metastasis-free survival (DMFS) in the training cohort. AHR modeling method divided NPC into six risk groups with significantly disparate survival ( p  < 0.001 for all): AHR1, T1N0; AHR2A, T1N1/T2-3N0 cfEBV DNA  < 2, 000 (EBVlow ); AHR2B, T1N1/T2-3N0 cfEBV DNA ⩾ 2, 000 (EBVhigh ) and T1-2N2/T2-3N1 EBVlow ; AHR3, T1-2N2/T2-3N1 EBVhigh and T3N2/T4N0 EBVlow ; AHR4, T3N2/T4 N0-1 EBVhigh and T1-3N3/T4N1-3 EBVlow ; AHR5, T1-3N3/T4 N2-3 EBVhigh . Our AHR model outperformed the published RPA models and TNM stage with better hazard consistency (1.35 versus 3.98–12.67), hazard discrimination (5.29 versus 6.69–13.35), explained variation (0.248 versus 0.164–0.225), balance (0.385 versus 0.438–0.749) and C-index (0.707 versus 0.662–0.700). In addition, our AHR model was superior to the TNM stage for risk stratification of OS in two validation cohorts ( p  < 0.001 for both). Conclusion: Herein, we developed and validated a risk classification system that combines the AJCC/UICC 8th edition TN-stage classification and cfEBV DNA for non-metastatic NPC. Our new clinicomolecular model provides improved OS prediction over the current staging system.